The Influence of Brand Equity Dimensions on Donor’s Decisions in Paying Alms - Syafiratud Daniyas; Andriani Samsuri; Lilik Rahmawati (Management of Zakat and Waqf Journal (MAZAWA), 2023)
The purpose of this research is to analyze the influence of brand equity dimensions simultaneously and also partially on donors' decisions in giving alms at UPZIS NU CARE-LAZISNU MWCNU Wonocolo. The method of analysis of this research is quantitative with the technical analysis tool used is multiple linear regression, to determine the direction and how much influence the independent variables have on the dependent variable. This research is using primary data obtained from the results of filling out the questionnaire. Based on the findings of data analysis using SPSS version 26, it shows that brand awareness and brand loyalty factors have a significant influence on the choice of donors partially. In addition, the brand equity aspect also has a simultaneous impact on donors' decisions to make donations at UPZIS NU CARE-LAZISNU MWCNU Wonocolo. This research, is expected that UPZIS NU CARE-LAZISNU MWCNU Wonocolo will continue to improve and maintain the brand that has been built.